ok so here u go
Simplifying
6(2x + -11) + 15 = 21 Reorder the terms:
6(-11 + 2x) + 15 = 21
(-11 * 6 + 2x * 6) + 15 = 21
(-66 + 12x) + 15 = 21 Reorder the terms:
-66 + 15 + 12x = 21 Combine like terms: -66 + 15 = -51
-51 + 12x = 21 Solving
-51 + 12x = 21
Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right.
Add '51' to each side of the equation.
-51 + 51 + 12x = 21 + 51
Combine like terms: -51 + 51 = 0
0 + 12x = 21 + 51
12x = 21 + 51 Combine like terms: 21 + 51 = 72
12x = 72
Divide each side by '12'.
x = 6
Simplifying
x = 6